2012
DOI: 10.1111/j.1467-8659.2012.03230.x
|View full text |Cite
|
Sign up to set email alerts
|

Vega: Non‐Linear FEM Deformable Object Simulator

Abstract: This practice and experience paper describes a robust C++ implementation of several non‐linear solid three‐dimensional deformable object strategies commonly employed in computer graphics, named the Vega finite element method (FEM) simulation library. Deformable models supported include co‐rotational linear FEM elasticity, Saint–Venant Kirchhoff FEM model, mass–spring system and invertible FEM models: neo‐Hookean, Saint–Venant Kirchhoff and Mooney–Rivlin. We provide several timestepping schemes, including impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 18 publications
0
55
0
Order By: Relevance
“…Our linear subspace can be directly applied in any simulator which supports model reduction [Sin et al 2013]. In our system we opted for a simpler yet effective approach: we augment the ARAP energy above with a momentum term [Chao et al 2010;Martin et al 2011;Jacobson 2013].…”
Section: Elastic Deformations With Dynamicsmentioning
confidence: 99%
“…Our linear subspace can be directly applied in any simulator which supports model reduction [Sin et al 2013]. In our system we opted for a simpler yet effective approach: we augment the ARAP energy above with a momentum term [Chao et al 2010;Martin et al 2011;Jacobson 2013].…”
Section: Elastic Deformations With Dynamicsmentioning
confidence: 99%
“…The timestep size is set to 20ms. Vega Library [BSS12,SSB13] is used to compute the tangent stiffness matrix and the internal force resulting from W StV K . The collision and global motion are treated by the method proposed in [HSO03].…”
Section: Methodsmentioning
confidence: 99%
“…Invertible FEM [Irving et al 2004] improved simulation robustness in scenarios involving extreme compression, while modified Newton methods [Teran et al 2005a] reduced the cost of implicit schemes with large time steps. Several of these algorithms have been incorporated in open-source modeling and simulation packages [Sin et al 2013]. Solutions have also been proposed for material behaviors such as incompressibility [Irving et al 2007] and viscoelasticity [Goktekin et al 2004;Wojtan and Turk 2008], both of which can be found in typical biomaterials.…”
Section: Related Workmentioning
confidence: 99%